2014
DOI: 10.1007/s10708-014-9594-2
|View full text |Cite
|
Sign up to set email alerts
|

The regional ecology of elderly falls in Sweden

Abstract: The study assesses exploratory the geography of the elderly fall in Sweden in relation to the ecology of the socio-demographic characteristics of the Swedes older population. Kendall Test is used to measure the association between elderly fall rates and demographic, socio-economic characteristics of the population, costs of elderly care and accessibility measures at county level. Results show a number of significant associations: high rates of the elderly fall are associated with high cost of the elderly care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Similarly, evidence from a report of the Australian Institute of Health and Welfare revealed that the rate of fall-related hospitalisation among older adults (≥ 65) during 2001–2003 for migrants from New Zealand, the United Kingdom, Ireland, the United States, Canada and South Africa and migrants from other countries, numbered at 2,070.3 and 1,788.6 per 100,000 population, respectively, both significantly lower than that of the Australia-born population (i.e., 2,498.1 per 100,000 population) [ 13 ]. Similar findings were documented in Sweden, showing a relatively low fall rate in Swedish counties with a high proportion of overseas-born older adults [ 14 ]. In contrast, a population-based study conducted in the communities of South Australia reported no difference in fall risk between Australia-born older adults (≥ 65) and older immigrants from overseas English-speaking countries (odd ratio [OR] = 0.95, 95% CI = 0.76–1.18), though immigrants from non-English-speaking countries had a lower fall risk than the Australia-born older adults (OR = 0.53 [95% CI = 0.38–0.74) [ 15 ].…”
Section: Introductionsupporting
confidence: 85%
“…Similarly, evidence from a report of the Australian Institute of Health and Welfare revealed that the rate of fall-related hospitalisation among older adults (≥ 65) during 2001–2003 for migrants from New Zealand, the United Kingdom, Ireland, the United States, Canada and South Africa and migrants from other countries, numbered at 2,070.3 and 1,788.6 per 100,000 population, respectively, both significantly lower than that of the Australia-born population (i.e., 2,498.1 per 100,000 population) [ 13 ]. Similar findings were documented in Sweden, showing a relatively low fall rate in Swedish counties with a high proportion of overseas-born older adults [ 14 ]. In contrast, a population-based study conducted in the communities of South Australia reported no difference in fall risk between Australia-born older adults (≥ 65) and older immigrants from overseas English-speaking countries (odd ratio [OR] = 0.95, 95% CI = 0.76–1.18), though immigrants from non-English-speaking countries had a lower fall risk than the Australia-born older adults (OR = 0.53 [95% CI = 0.38–0.74) [ 15 ].…”
Section: Introductionsupporting
confidence: 85%
“…Further research could bring more knowledge and awareness about the effects and importance of housing adaptations in terms of quality of life, economic costs and social sustainability. A study by Bamzar (2017) shows, for example, ‘distance decay’ concerning elderly people´s perception of safety. The consequence of this is that elderly people's perceived safety is closest to the housing environment and decreases when the distance increases.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies in residential environment injuries have included elderly people with disabilities and chronic diseases, to report on their coping strategies. One study investigated elderly mobility and safety issues for elderly people and what this issue means for elderly people in different kind of environments (Bamzar, 2017). Bamzar argue: ‘One immediate answer could be that safety perception is an outcome of both emotional and physical comfort.…”
Section: Significance Of the Residential Living Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Exports from the agricultural sector may help the economy diversify away from a restricted range of goods, freeing up capital for infrastructure and social services investments. Countries with a high agricultural dependency but poor crop yields often have a smaller trade surplus, fewer economic prospects, and a weaker ability to pursue development projects [1][2][3][4][5][6][7][8][9][10].…”
Section: Impact Of Crop Yields On Socio-economic Developmentmentioning
confidence: 99%